Financial liberalization, innovation and the response of Malaysian commercial banks’ portfolios to monetary shocks - Noor Azlan Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 1999)
Several recent theoretical papers have shown that banking institutions posses a special role in the transmission mechanism of monetary policy. The reactions of banks toward changes in monetary conditions, particularly their portfolio allocations, determine the ultimate impact of monetary policy on real activities. In addition, several findings also indicate the changing behaviour of commercial banks in recent years due to the development of financial markets and liberalization process which begin since early eighties. This paper examines this issue for the Malaysian banking industry. Without exception, liberalization and innovation that occur in the Malaysian financial industry since early eighties also affect the way banks respond to changes in monetary policy. It is shown that banks resort to competitive funds and securities liquidation in their attempt to shield the lending capacity. This is made possible by the recent development in the banking industry. It is argued that the central bank loses to some extent, its direct influence on banks portfolio allocations, thus, reducing the effectiveness of monetary policy. Studying the transmission mechanism of monetary policy, therefore requires special attention to the behaviour of banking firms